Intraabdominal Compartment Syndrome Complicating Transurethral Resection of Bladder Tumor. (21st August 2012) - Narain, Sachin; Giquel, Jadelis; Ariza, Armando; Martinez-Ruiz, Ricardo; Kava, Bruce R.; Matadial, Christina
Abstract : Abdominal compartment syndrome can result from many different causes. We present a case where this dangerous syndrome occurred in the operating room during a transurethral resection of a bladder tumor. It was initially recognized by an elevation in the peak inspiratory pressure. We report the typical physiologic changes that occur with this syndrome and its treatment options.